Student-Centered Learning In ‘The School of Rock’ Movie Directed By Richard Linklater - Iwan Pranoto (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2022)
One of the teachers in the ‘School of Rock’ movie is characterized uniquely compared to the others. Instead of being like a teacher normally does, the main character of this movie is a member of a band who disguises himself as a teacher. He once pretends to be his friend who applied as a teacher in that certain school. Categorized as a comedy movie, it does not have a serious plot but is a lot of fun. Nevertheless, an interesting thing pops up about how the main character, Deway, teaches art through his ‘own way of teaching’. To analyze this movie deeper, the researcher used a literature review as a data collection. This article was then presented by using a narrative method that is by breaking down each element thoroughly and educational approach through Herbert Read’s art. By completing this article, it is expected to see the interrelation between the elements building the art with its comprehensive meaning